2000
DOI: 10.1016/s0378-1097(00)00424-9
|View full text |Cite
|
Sign up to set email alerts
|

Production of Shiga toxin by Escherichia coli measured with reference to the membrane vesicle-associated toxins

Abstract: Production of Shiga toxin (Stx) 1 and 2 from Stx-producing Escherichia coli (STEC) was measured with reference to the membrane vesicle (MV)-associated toxins. An immunoblot analysis method using specific antibodies for Stx1 and Stx2 was developed for the detection of the extracellular toxins. All 46 STEC isolates, studied including 30 O157 and 16 other O-antigenic isolates, released Stx1 and Stx2 as MVassociated and MV-removed fractions under aerobic and anaerobic conditions. Treatment of vesicles with polymyx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…The MVs were confirmed as round projections on or around bacterial cells by immunoelectron microscopy (13,14,21). Extracellular toxins of Escherichia coli are produced during the exponential growth phase and are released into the growth medium as the MV form (28). In this study, many fragments were observed on the surface of F. psychrophilum.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The MVs were confirmed as round projections on or around bacterial cells by immunoelectron microscopy (13,14,21). Extracellular toxins of Escherichia coli are produced during the exponential growth phase and are released into the growth medium as the MV form (28). In this study, many fragments were observed on the surface of F. psychrophilum.…”
Section: Discussionsupporting
confidence: 52%
“…The virulence of bacteria often varies according to culture conditions, such as temperature, pH, NaCI concentration, nutritional substances, and culture age (6,12,19,24,28). Thus the culturing period is an important factor that may alter the virulence of pathogenic bacteria.…”
mentioning
confidence: 99%
“…OM vesicles from Actinobacillus actinomycetemcomitans exhibit cytotoxicity (22,73,105), and Xenorhabdus nematophilus and Photorhabdus luminescens OM vesicles were cytotoxic for insect larvae as well as in tissue culture (79). Kolling and Matthews demonstrated, by immunoblotting, that Shiga toxin is present inside OM vesicles produced by O157:H7 cells (81), and this was corroborated for many strains of Shiga toxinproducing E. coli (STEC) under both aerobic and anaerobic conditions (143). NarE is a putatively vesicle-associated protein of Neisseria meningitidis vesicles that exhibits ADP-ribosyltransferase and NAD-glycohydrolase activities typically associated with toxicity (93).…”
Section: Vesicle-associated Toxinsmentioning
confidence: 96%
“…The bacterial strains and plasmids used in this study are listed in Table 1. NGY9 was an isolate of the Sakai outbreak and the isolation of an isogenic rpoS ‐deficient mutant from NGY9 was performed as described previously (Yokoyama et al , 2000). All strains were stored at –80°C in 20% glycerol.…”
Section: Methodsmentioning
confidence: 99%